Development of Wireless Robotic Stakeout System based on ZigBee Transceiver Modules - SARWAR, MUHAMMAD BILAL (2016)
Wireless technology has become a new emerging technology in stakeout and security concerned industries. Study of robot communication with energy efficiency is also one of the important research area. Therefore this research work presents an efficient computerized robotic vehicle (CRV) for stakeout and recognition purposes with the use of energy efficient ZigBee based transceiver. The designed model entails a combination of programmable microcontrollers, relay circuitry, DC motors and sharp camera eyeto control the robotic vehicle through another wireless transceiver module which is connected with personal computer. In the operation of each sensor node in wireless and movable stakeout system, battery is also an important limiting factor for the whole system performance and lifetime so it is obtained that ZigBee transponders are capable in providing wider transmission range and are efficient compare to RF and Wi-Fi, due to low usage of power during data gathering transmission.